2023
DOI: 10.3389/fonc.2023.1059520
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis open a new door for colorectal cancer treatment

Abstract: Colorectal cancer (CRC) is the third highest incidence and the second highest mortality malignant tumor in the world. The etiology and pathogenesis of CRC are complex. Due to the long course of the disease and no obvious early symptoms, most patients are diagnosed as middle and late stages. CRC is prone to metastasis, most commonly liver metastasis, which is one of the leading causes of death in CRC patients. Ferroptosis is a newly discovered cell death form with iron dependence, which is driven by excessive l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 130 publications
0
7
0
Order By: Relevance
“…This suggests that the induction of iron-mediated cell death could serve as a therapeutic approach for CRC, particularly against drug-resistant CRC that is resistant to conventional medical interventions. 155,156 Several small molecule compounds derived from plants have demonstrated their ability to induce ferroptosis in CRC. Ginsenosides Rh4 and auriculasin were capable of inducing the accumulation of ROS and the onset of ferroptosis.…”
Section: Prostate Cancer (Pc)mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the induction of iron-mediated cell death could serve as a therapeutic approach for CRC, particularly against drug-resistant CRC that is resistant to conventional medical interventions. 155,156 Several small molecule compounds derived from plants have demonstrated their ability to induce ferroptosis in CRC. Ginsenosides Rh4 and auriculasin were capable of inducing the accumulation of ROS and the onset of ferroptosis.…”
Section: Prostate Cancer (Pc)mentioning
confidence: 99%
“…CRC cells, especially those with drug-resistant properties, exhibit elevated levels of iron and ROS. This suggests that the induction of iron-mediated cell death could serve as a therapeutic approach for CRC, particularly against drug-resistant CRC that is resistant to conventional medical interventions. , Several small molecule compounds derived from plants have demonstrated their ability to induce ferroptosis in CRC. Ginsenosides Rh4 and auriculasin were capable of inducing the accumulation of ROS and the onset of ferroptosis. , Treatment of CRC with punicic acid increased intracellular LPO, and when combined with docosahexaenoic acid, the cytotoxicity of punicic acid was synergistically enhanced .…”
Section: Ferroptosis Inducers and Their Application In Cancer Therapymentioning
confidence: 99%
“…Another burgeoning area of research is the potential influence of the gut microbiome in shaping the resistance to immunotherapy. [ 59 ] Recent research has illuminated the possibility that specific microbiota residing in the gut may have the capacity to shape immune responses, thereby influencing the effectiveness of immunotherapy. Understanding the complex interactions between the gut microbiome and the immune system could potentially unlock novel strategies for microbiome modulation, thereby enhancing the efficacy of immunotherapy.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Ferroptosis, which inhibits tumor proliferation and induces ferroptosis, has demonstrated efficacy in reversing drug resistance. [ 3 ] Recently, we found that talaroconvolutin A, which was first discovered by Kawai and coworkers from Talaromyces convolutus as an antifungal, [ 4 ] could kill colon cancer cells by inducing ferroptosis (HCT116, IC 50 1.22 μM; SW480, IC 50 1.40 μM; SW620, IC 50 1.27 μM). [ 5 ] The potency of talaroconvolutin A in inhibiting colon cancer cells via ferroptosis is considerably higher than that of erastin (a well‐known ferroptosis inducer), making it a novel candidate for CRC therapy resistance.…”
Section: Background and Originality Contentmentioning
confidence: 99%